Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.7567/apex.8.105001
|View full text |Cite
|
Sign up to set email alerts
|

Crossover from Efros–Shklovskii variable range hopping to nearest-neighbor hopping in silicon nanocrystal random network

Abstract: We investigate how random structure affects the electrical transport of a silicon nanocrystal network. The temperature dependence of conductivity follows G ∼ exp[−(T0/T)1/2] between 70 and 160 K. By using T0 = 5765 K obtained by data fitting, the electron localization length is estimated to be 4.1 nm, which corresponds to the mean diameter of silicon nanocrystals. Above 160 K, G follows Arrhenius-like behavior. These temperature dependences are well described by Efros–Shklovskii variable range hopping (ES VRH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Due to this Coulomb gap between two interacting electrons, the density of states become nearly equal to zero near the Fermi level [40,41]. As a result, the logarithmic resistivity follows the linear dependency on T −1/2 (ES-VRH) instead of T −1/3 (Mott-VRH) [42,43]. Figures 6(c (ES-VRH).…”
Section: X-ray Photoelectron Spectroscopy and Origin Of Charge Transfermentioning
confidence: 96%
“…Due to this Coulomb gap between two interacting electrons, the density of states become nearly equal to zero near the Fermi level [40,41]. As a result, the logarithmic resistivity follows the linear dependency on T −1/2 (ES-VRH) instead of T −1/3 (Mott-VRH) [42,43]. Figures 6(c (ES-VRH).…”
Section: X-ray Photoelectron Spectroscopy and Origin Of Charge Transfermentioning
confidence: 96%
“…Wienkes et al reported the transport property of phosphorus (P) doped amorphous/nanocrystalline silicon thin films and observed a crossover from Mott variable-range hopping (VRH) to multiphonon hopping (MPH) at about 50 K [20]. Inada et al observed a crossover from Efros-Shklovskii (E-S) VRH to nearest-neighbor hopping at 160 K in crystallized Si random network [21]. Additionally, Chen et al revealed the E-S VRH process of P-doped free-standing Si NCs in the temperature range of 80-300 K, and predicted the critical carrier concentration of metal-insulator transition (MIT) in Si NCs [22].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the SAD may occur for different reasons. At high it could indicate the nearest neighbor hopping (NNH) [23,[34][35][36], or a band conductivity [6,37]. At low , however, the probability of both the NNH and band conductivity becomes negligibly small.…”
Section: Introductionmentioning
confidence: 99%